2016
DOI: 10.1136/bmjquality.u206760.w3983
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Sepsis in the Emergency Department- Identifying Barriers to Delivery of the Sepsis 6

Abstract: The Sepsis 6 is an internationally accepted management bundle that, when initiated within one hour of identifying sepsis, can reduce morbidity and mortality. This management bundle was advocated by the Scottish Patient Safety Programme as part of its Acute Adult campaign launched in 2008 and adopted by NHS Tayside in 2012. Despite this, the Emergency Department (ED) of Ninewells Hospital, a tertiary referral centre and major teaching hospital in Scotland, was displaying poor success in the Sepsis 6.We therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
(14 reference statements)
2
11
0
Order By: Relevance
“…Several projects have used a combination of education, checklists and stickers, sepsis "champions" and sepsis "packs". [14][15][16][17] These combinations of interventions are labour intensive and require sustained implementation to work. A systematic analysis of the effect of performance improvement programmes on compliance with sepsis bundles found that education and process change can successfully improve compliance, and showed a concomitant reduction in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several projects have used a combination of education, checklists and stickers, sepsis "champions" and sepsis "packs". [14][15][16][17] These combinations of interventions are labour intensive and require sustained implementation to work. A systematic analysis of the effect of performance improvement programmes on compliance with sepsis bundles found that education and process change can successfully improve compliance, and showed a concomitant reduction in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…decrease in number of duplicate blood chemistry tests per 100 ED visits (p<0.0001), reduction in both the daily number of laboratory studies (−36.3%; p<0.05), 18 (p<0.0001) 28 and in POC tests (p<0.0001); 28 iii) protocols compliance, i.e. reported by Bentley et al 8 with an 74.3% improvement of sepsis detection and management, by Hecker et al 13 with an increase from 44 to 68% to adherence to cystitis and pyelonephritis management guidelines, and to confidence by the operators. With regard to this last point, Scott et al 29 reported that 100% of the participants were more likely to identify the indication for Indwelling Urethral Catheterization (IUC) insertion and to use incontinence pads (72%), commodes (84%), straight catheterization (78%), urinals/bedpans (89%), and restrooms (67%) as alternatives to IUCs after the intervention; 84% changed the way they approached bladder management in their practice after the intervention; 83% were more likely to rethink the use of IUCs among patients with altered mental status, inpatient boarders, and nursing home patients.…”
Section: Reviewmentioning
confidence: 71%
“…All 24 studies followed the before/after scheme and 5 have a Plan-Do-Study-Act (PDSA) design. [8][9][10]22 While 9 studies involved different medical departments, 6,[10][11][12]17,19,21,22,27 15 of them concerned only Emergency departments and/or paramedics. Most of articles proposed a multimodal approach: only 7 of them concerned exclusively A&F. [7][8][9][10][11]13,22 As it's shown in Table 2, 9 articles talked about measurements for infective pathologies (especially antibiotic stewardship), 7,8,12,13,16,17,21,22,29 6 of them treated cardiac arrest or cardiovascular emergency problems, 8,19,20,[25][26][27] 2 of them treated stroke, 15,24 3 ones were about laboratory analyses 10,18,28 and 4 of them treated any other fields (diabetic ketoacidosis, use of a prothrombin complex, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies report similar barriers. A study [21] found that doctors and nurses demonstrated difficulty in identifying septic patients. Results of a cross sectional descriptive study using a self-completed questionnaire given to doctors and nurses related to sepsis identification, principles, resources, skill and education demonstrated that there was a lack of adequate nursing staff, and resources to deliver interventions within the hour [22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%